A vezetés új kihívásai a XXI. században - Berde, Csaba (Közép-Európai Közlemények, 2013)
Owing to the economic crisis, the XXI. century started with excessively dynamic change procedures and after almost a decade, consolidate, stable state has not been established. Permanent changes keep organizations continuously in the state of instability. The management itself has to deal with this situation and lead organizations in this extremely dynamic, uncertain position. We must admit that organizational uncertainty is a natural state of XXI. century enterprises. This study also analyzes how new understanding of environmental effects appears in the evolutionary approach of thinking. We also interpret predictability in the XXI. century economic procedures. Considering organic approach and way of thinking, we must talk about organic organizations, indeed. New structural elements, such as project, the „ad hoc” group, the team raise new managerial problems.